Javno mnenje in stališča parlamentarnih strank do članstva v EU v Republiki Češki - Brokl, Lubomír (Teorija in praksa, 2000)
This article examines the development of attitutes towards EU membership in the Czech Republic. After the "Velvet revolution," EU membership became one of the symbols for democracy and solidified new political orientations. The attitudes of Czech citizens towards EU membership can be distinguished into three periods according the development of domestic politics as well as according to social and interest-group differenciation. The first period lasted until the split of Czechoslovakia, the second one is defined as beginning from the emergence of Czech Republic until the 1996 parliamentary election. The third period is contemporary and could be characterised beneficially by economic problems, the exchange of political suits and recognition of the impact of entering the EU for the country. The more exact (and the more relevant to the interests of individual classes and groups of citizens) the question is, the greater are the doubts. If the respondents must decide in favor or against membership in the EU, however, they always decide in favour of Europe.
Keywords: javno mnenje; political party; politične stranke; European Union; Evropska unija; Czech Republic; Češka; članstvo